Risk Factors Affecting Multi-Drug Resistant Tuberculosis in Surakarta and Ngawi, Indonesia - Novi Indah Aderita; Bhisma Murti; Nunuk Suryani (Masters Program in Public Health, 2016)
Background: The success rate of Tuberculosis treatment in Indonesia decreased by 81.3% in 2014, which below the 85% target. The current increasing problem in the developing world is multidrug resistance of Tuberculosis (MDR-TB). Many factors may contribute to MDR-TB. At the individual level these factors may include adherence to medication, perception of vulnerability, seriousness, benefit, barrier, and nutritional status. At the institutional level these factors may include the availability of drugs and implementation of DOTS program. This study aimed to analyze factors that affect MDR-TB in Surakarta and Wonogiri district, Central Java, Indonesia.Subjects and Method: This was an observasional analytic study with case control design. It was carried out in August-October 2016 in Surakarta and Ngawi, Indonesia. A total of 120 patients were selected by fixed disease sampling. Another sample of 44 health workers was also selected for the study. The endogenous variables: adherence, nutritional status, and implementation of the treatment of DOTS. The exogenous variables: perception of vulnerability, seriousness, benefits, barriers, the availability of anti Tuberculosis drugs. The data was collected by questionnaire and analyzed by path analysis.Results: Nutritional status (b=-2.98; 95% CI =-5.31 to -0.64; p = 0.012), adherence to anti Tuberculosis drugs (b=-3.38; 95% CI =-5.94 to -0.82; p = 0.010), treatment with DOTS for MDR TB (b=-0.88; 95% CI = 1.43-3.18 ; p = 0.456) were associated with MDR-TB. Perceived vulnerability (b= 2.81; 95% CI= 0.99 to 4.64; p = 0.003), seriousness (b=4.47; CI 95% = 2.38 to 6.57; p 0.001), benefits (b= 3.4; CI 95%= 1.52 to 5.18; p=0.001), barriers (b =-1.81; 95% CI=-3.48 to -1.39; p=0.034), as well as availability of DOTS treatment (b = 3.14; CI 95% = 0.95 to 5.32; p = 0.002), were associated with adherence to treatment.Conclusion: Nutritional status, adherence to treatment, implementation of DOTS strategy for MDR-TB affect the risk of MDR TB. Perceived vulnerability, seriousness, benefit, and barrier, as well as availability of DOTS treatment, affect adherence to treatment. Partnership between patients and health care personnel is recommended to increase the success of TB treatment.Keywords: tuberculosis, risk factor, MDR-TB, adherence to treatmentCorrespondence: Novi Indah Aderita. Polytechnic of Health Sciences Bhakti Mulia, Sukoharjo, Central Java Email: adherita_alhaniin@yahoo.comJournal of Health Promotion and Behavior (2016), 1(2): 86-99https://doi.org/10.26911/jepublichealth.2016.01.02.02